2014
DOI: 10.12816/0018952
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perception of the Roles of Guidance Counsellors in Secondary Schools in Rivers State

Abstract: The study investigated teachers' perception of the roles of Guidance Counsellors in secondary schools in Rivers State, Nigeria. Simple random sampling technique was adopted to select three hundred and seventy (370) male and female secondary school teachers from a population of five thousand three hundred school teachers. The "School Teachers' Perception of Guidance Counsellors Rating Scale" (STPRGCRS) was administered to the respondents to collect necessary data. The t-test statistics was used to test three nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This study found that male and female teachers have a high perception towards guidance counsellors' tasks performance in secondary schools in Anambra State. This findings supports that of Eremie (2014), who found that male and female teachers perceived that counsellors to adequately guide students to resolve their personal-socio problems. The finding also revealed that male and female teachers perceived counsellors to guide students towards their vocational guidance needs.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…This study found that male and female teachers have a high perception towards guidance counsellors' tasks performance in secondary schools in Anambra State. This findings supports that of Eremie (2014), who found that male and female teachers perceived that counsellors to adequately guide students to resolve their personal-socio problems. The finding also revealed that male and female teachers perceived counsellors to guide students towards their vocational guidance needs.…”
Section: Discussion Of Findingssupporting
confidence: 89%
“…Eremie ( 2014 ) and Egenti ( 2018 ) indicated that teachers’ perceptions confirmed that counselors positively afford educational and emotional services. Here, there were no significant differences between male and female teachers based on the variable of years of experience and gender.…”
Section: Literature Reviewmentioning
confidence: 98%
“…A study conducted by Eremie (2015) investigated teachers' perceptions of the role of Guidance Counselors in secondary schools in Rivers State, Nigeria. A simple random sampling technique was adopted to select three hundred and seventy (370) male and female secondary school teachers from a population of five thousand three hundred school teachers.…”
Section: Culture/ Environmentmentioning
confidence: 99%
“…In the study, it was stated that guidance activities in schools should refer to Frank Parson's theory which focuses on the purpose of guidance services to guide individuals in making choices of teaching and learning activities in the classroom and to prepare individuals to get into a particular world of work. Guidance counselors are tasked with helping individuals make choices in selecting and planning course options in the school environment (Eremie, 2015). The teachers who were respondents in the study were more likely to view school counselors as helping students solve problems related to socio-emotional issues while classroom teachers themselves were the ones who helped students, especially in cognitive or learning-related matters.…”
Section: Culture/ Environmentmentioning
confidence: 99%